2012
DOI: 10.1097/scs.0b013e3182420575
|View full text |Cite
|
Sign up to set email alerts
|

Primary Malignant Melanoma of the Nasal Cavity

Abstract: Primary malignant melanoma of the nose and paranasal sinus mucosa is a rare disease and seen in less than 1% among all melanomas. Malignant melanomas have 2 origins: cutaneous and mucosal. The mucosal form has a worse prognosis because of its aggressiveness compared with that of the cutaneous form. Mucosal melanomas often occur at a rate of 2% to 3% among all melanomas and are typically found in the nasal cavity and paranasal sinuses. Generally, it is more common in males and in those older than 50 years. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 6 publications
1
20
0
Order By: Relevance
“…Primary mucosal sinonasal melanoma is rare, comprising less than 1% of melanomas 7. A metachronous primary sinonasal mucosal melanoma was considered but thought to be highly unlikely in this case.…”
Section: Discussionmentioning
confidence: 86%
“…Primary mucosal sinonasal melanoma is rare, comprising less than 1% of melanomas 7. A metachronous primary sinonasal mucosal melanoma was considered but thought to be highly unlikely in this case.…”
Section: Discussionmentioning
confidence: 86%
“…Göçmen et al detected tbc lymphadenitis in 14 of 112 (12.5%) NMs. 18 9,11,19 They concluded that tbc lymphadenitis was the most common cause of NMs among inflammatory cases. On the other hand, Kırış et al reported tbc lympadenitis as the second most common cause of NMs after reactive lymphadenitis.…”
Section: Discussionmentioning
confidence: 99%
“…Epistaxis and nasal obstruction were the most frequent presenting symptoms in reported series 3,9,11) . The prominent symptoms were also epistaxis and nasal obstruction in our patients.…”
Section: Many Studies That Investigated Only Patients With Intranasalmentioning
confidence: 99%
“…However, we believe that negative surgical margins and clearing foci such as mucosal maculation areas are important criteria for treatment success. The precise etiopathogenesis is unknown, with one study suggesting that tobacco use and formaldehyde exposure may play a role 11) .…”
Section: Many Studies That Investigated Only Patients With Intranasalmentioning
confidence: 99%